2020
DOI: 10.3390/nu12040948
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium breve UCC2003 Exopolysaccharide Modulates the Early Life Microbiota by Acting as a Potential Dietary Substrate

Abstract: Background: Bifidobacterium represents an important early life microbiota member. Specific bifidobacterial components, exopolysaccharides (EPS), positively modulate host responses, with purified EPS also suggested to impact microbe–microbe interactions by acting as a nutrient substrate. Thus, we determined the longitudinal effects of bifidobacterial EPS on microbial communities and metabolite profiles using an infant model colon system. Methods: Differential gene expression and growth characteristics were dete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…For example, high-molecular-weight EPS is more likely to induce weaker immune responses, potentially because these encapsulating structures shield the complex protein antigens on the bacterial surface from interaction with immune cells ( 51 ). Furthermore, a specific EPS from B. breve has been shown to be metabolized by some members of the infant gut microbiota, indicating that EPS further facilitates cross-feedings between gut bacteria ( 52 ). Therefore, the considerable diversity shown by different EPS genomic characterizations in our B .…”
Section: Discussionmentioning
confidence: 99%
“…For example, high-molecular-weight EPS is more likely to induce weaker immune responses, potentially because these encapsulating structures shield the complex protein antigens on the bacterial surface from interaction with immune cells ( 51 ). Furthermore, a specific EPS from B. breve has been shown to be metabolized by some members of the infant gut microbiota, indicating that EPS further facilitates cross-feedings between gut bacteria ( 52 ). Therefore, the considerable diversity shown by different EPS genomic characterizations in our B .…”
Section: Discussionmentioning
confidence: 99%
“…One cluster (epsRhm) was found to include genes that are putatively responsible for rhamnose biosynthesis, whereas the second cluster (eps) presents two adjacent oppositely oriented genes (eps1 and eps2), encodes regulatory components, glycosyltransferases and export functions (Fanning et al, 2012b). According to previous studies, B. breve UCC2003 EPS, metabolized by members of the infant microbiota, promotes the health status of infants (Pungel et al, 2020) and downregulates apoptotic responses to protect epithelial cells under imposed inflammatory conditions (Hughes et al, 2017), supporting the notion that EPS-mediated immune response is influenced by the physicochemical nature of these polymers.…”
Section: Exopolysaccharidesmentioning
confidence: 99%
“…Recent studies have shown that infant-type bifidobacteria present different cell surface structures, such as exopolysaccharides (EPSs) and pili/fimbriae, allowing bifidobacteria to colonize the infant’s gut, adhere to intestinal cells and participate in the development of the host immune system [ 66 , 67 ]. Consequently, the administration of EPSs from B. breve UCC2003 might serve as a new strategy for promoting infant health [ 68 ]. In addition, EPSs produced by B. longum subsp.…”
Section: Infant-type Bifidobacteria Affect the Establishment Of Immun...mentioning
confidence: 99%